Impact of in utero drug exposure on neonates requiring ECMO: A retrospective cohort study - Hallie Walther; Aric Schadler; Karen Garlitz; Karen Garlitz; John A. Bauer; Lindsay Kohler; Erika Waldsmith; Hubert O. Ballard (Frontiers in Pediatrics, 2023)
The incidence of in utero drug exposure (IUDE) and neonatal extracorporeal membrane oxygenation (ECMO) utilization have both increased over the past decade. However, there are no studies to date that examine the impact that IUDE has on neonates requiring ECMO. In this retrospective cohort study, we compared the clinic course and outcomes of neonates who were placed on ECMO with IUDE vs. neonates without IUDE. Analysis included data extracted from medical records from all neonatal ECMO runs between January 2014 and January 2021 at the University of Kentucky Children's Hospital. A total of 56 neonatal patients were placed on ECMO during this time period and there were a total of 57 ECMO runs. Nearly one-third of neonates (16) had documented IUDE. There were no differences in gestational age, length of ECMO run, survival to discharge, or number of major complications while on ECMO in the neonates with IUDE compared to those without. In contrast, greater use of sedative and analgesic adjuvant medications during ECMO was required for IUDE-ECMO cases (p < 0.01). Trending results indicated that post-ECMO feeding complications and total hospitalization length were also greater in the IUDE-ECMO group. These findings illustrate the complex influence of prenatal drug exposures on neonatal patient care and warrant the development of clinical care strategies optimized for this unique patient group.